Health-Related Quality of Life and Use of Hospital Services by Patients with Heart Failure and Their Family Caregivers: A Multicenter Case-Control Study. - Timonet Andreu, Eva María; Morales-Asencio, José Miguel; Alcalá Gutierrez, Purificación; Cruzado Álvarez, Concepción; López-Moyano, G; Mora-Banderas, Ana María; López-Leiva, María Inmaculada; Canca-Sánchez, José Carlos (Wiley, 2020)
Background: Heart failure (HF) leads to high hospital admission rates. Disease progression affects the health-related quality of life (HRQoL) of patients and caregivers, but current evidence is largely from cross-sectional studies with limited samples. Objectives: To analyze the relationship between HF patients' hospital service use (as a proxy for disease progression) and the HRQoL of their family caregivers. Methods: This multicenter nested case-control study involved 530 patient-caregiver dyads from hospitals in southern Spain. Hospital admission data for the 5 years prior to inclusion were retrospectively collected. Associations between patient deterioration and caregivers' HRQoL were analyzed using bivariate analyses and multivariate logistic regression. Results: Increased hospital service use by patients was linked to worse caregiver HRQoL, with an overall OR of 1.48 (95% CI: 1.23–1.79). Positive correlations were found between patients' perceived physical health and caregivers' perceived mental health (r = 0.127, p = 0.004), and between the perceived mental health of both (r = 0.291, p < 0.0001). Conclusions: Greater hospital service use by HF patients independently predicts caregiver HRQoL deterioration. The physical and mental HRQoL of patients and caregivers interact, influencing each other. Additional factors, such as caregiving intensity, also contribute to caregiver HRQoL decline. Clinical Relevance: These findings highlight the need to identify family caregivers of HF patients at risk of HRQoL deterioration. Since increased hospital use predicts this decline, clinical nurses, as primary caregivers' supporters and educators, should tailor interventions to mitigate these effects.
Autorización en correo RIUMA (10/01/25)
Keywords: Insuficiencia cardíaca; Cuidadores - Aspectos psicológicos; Enfermos - Relaciones familiares; Heart failure; Burnout; Caregivers; Patients readmission; Psychological; Quality of life